New Canadian records of Nemastoma bimaculatum (Fabricius), and a brief summary of introduced Eurasian harvestmen in North America (Arachnida, Opiliones) - Shear, William A. (Zootaxa, 2016)
Eurasian harvestmen have been introduced to, and have established themselves in North America. Species known to have been introduced include Trogulus tricarinatus (L.) 1767, Paroligolophus agrestis (Meade) 1855, Rilaena triangularis (Herbst) 1799, Oligolophus tridens (C. L. Koch) 1836, and Nemastoma bimaculatum (Fabricius) 1775, for the last of which new Canadian records (Ontario) are given below. It is not entirely determined if the species Phalangium opilio (L.) 1758, Opilio parietinus (DeGeer) 1778 and Mitopus morio (Fabricius) 1779 are introduced to North America, or are naturally of Holarctic distribution. The former seems the more likely hypothesis for the first two, but M. morio in North America may be native or may not be that species. Detailed descriptions and illustrations of all these species may be found in Martens (1978).